A mold processing process for hot top casting of aluminum alloy
By adopting a new adhesive preparation method, combining graphite and talc powder, a refractory insulation material with high bond strength and thermal shock resistance is prepared, which solves the problem of existing materials falling off during the hot-top casting of aluminum alloys and ensures the normal progress of aluminum alloy casting.
Patent Information
- Application Number
- CN202411258227.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing refractory insulation materials have low bonding strength and poor thermal shock resistance during the hot-top casting of aluminum alloys, which leads to material falling off and surface defects such as horizontal folds, and may lead to aluminum hanging and process collapse, affecting the normal casting of aluminum alloys.
Using a new adhesive preparation method, carbonated in a carbon dioxide atmosphere is obtained by blending ethyl orthosilicate and 3-(methacryloyloxy)propyltrimethoxysilane, combined with chemical reaction of 3-mercaptopropionic acid and epoxypropane, to obtain a toughened modification of the adhesive. The adhesive is mixed with graphite and talc powder, as the main component of the refractory insulation material, and is coated at the connection between the graphite ring and the adapter plate of the hot-top casting crystallizer.
The bonding strength and thermal shock resistance of refractory insulation materials are improved, the problem of material falling off in high-temperature environments is avoided, the normal progress of the aluminum alloy casting process is ensured, and the occurrence of aluminum hanging and collapse is reduced.
Smart Images

Figure BDA0005034732040000111 
Figure BDA0005034732040000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy material processing, and in particular to a mold processing process for hot top casting of aluminum alloy. Background Art
[0002] The direct water-cooled semi-continuous casting process of aluminum and aluminum alloys has gone through five development stages, namely ordinary mold casting, short crystallizer casting, insulation mold casting, hot top casting and electromagnetic casting. Electromagnetic casting has not been widely used in process production due to its complex technical equipment, difficult operation and unsuitability for multi-mold casting. Hot top casting is currently the most widely used preparation method in the aluminum alloy casting industry. The surface quality of the ingots prepared by it is excellent, the problems of oxide entanglement and hydrogen absorption are eliminated, the work intensity is reduced, and the production efficiency of the enterprise is significantly improved. Hot top casting evolved from traditional direct cooling semi-continuous casting (DC casting). At first, a layer of refractory and heat-insulating asbestos was placed on the inner side of the crystallizer to form an insulating hot top on the upper part of the crystallizer. The aluminum liquid can only crystallize in the area of the lower part of the crystallizer that is not covered with refractory materials, which is conducive to the floating of bubbles and inclusions in the melt, inhibiting the entanglement of surface oxide slag, and thus improving the surface quality and density of the ingot to a certain extent. The currently common hot top casting crystallizer makes the aluminum melt in the insulation tank and the melt in the distribution tank form a horizontal plane, stabilizes the oxide film on the surface of the melt, eliminates problems such as oxide entanglement and hydrogen absorption, and significantly improves the purity of the melt.
[0003] In order to reduce the contact resistance between the melt and the inner wall of the crystallizer during the production process, a typical hot top casting crystallizer needs to continuously supply lubricating oil to the upper part. However, single lubrication cannot achieve the ideal state. The solidified billet shell and the crystallizer surface still have a large friction resistance, forming a unique continuous layered and sweat-like surface, which reduces the surface quality of the ingot. At the same time, the contact part between the crystallizer and the hot top is prone to metal leakage, causing production accidents. Before hot top casting of aluminum alloys, refractory insulation materials are usually used to fill the gap between the hot top tool adapter ring and the graphite ring, which plays a lubricating role during the hot top casting process to make the hot top cast ingot have better surface quality. However, in the prior art, talcum powder, graphite powder and a binder are generally used to prepare refractory thermal insulation materials. The refractory thermal insulation materials have low bonding strength and poor thermal shock resistance. During the aluminum alloy casting process, the refractory thermal insulation materials fall off, which not only affects the aluminum alloy casting and causes surface defects such as horizontal wrinkles of the aluminum alloy, but also causes aluminum hanging at the junction of the graphite ring and the adapter plate. As the amount of aluminum hanging increases, the solidified shell of the ingot is destroyed, and the molten metal in the aluminum hanging area leaks without forming a shell, causing a process collapse phenomenon, which affects the normal casting of the aluminum alloy. Summary of the invention
[0004] The object of the present invention is to provide a mold processing process for hot top casting of aluminum alloy to solve the following technical problems:
[0005] The existing refractory insulation materials have low bonding strength and poor thermal shock resistance, which causes the refractory insulation materials to fall off during the aluminum alloy casting process. Not only does the cast aluminum alloy have surface defects such as horizontal wrinkles, but it also causes aluminum hanging at the junction of the graphite ring and the adapter plate, causing process collapse and affecting the normal casting of the aluminum alloy.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A mold processing process for hot top casting of aluminum alloys comprises the following steps: coating a refractory heat-insulating material on the surface of the connection between a graphite ring and an adapter plate of a hot top casting crystallizer;
[0008] The refractory heat-insulating material comprises the following raw materials in parts by weight: 50-80 parts by weight of refractory aggregate, 15-25 parts by weight of binder, and 2-5 parts by weight of suspending agent;
[0009] The preparation method of the adhesive comprises the following steps:
[0010] S1: adding vinyl silicone component, 3-mercaptopropionic acid, azobisisobutyronitrile and anhydrous ethanol into a reaction kettle and dispersing them evenly to obtain component 1;
[0011] S2: Add component 1, epichlorohydrin and benzyltriethylammonium chloride into a reaction kettle and disperse evenly, heat to 100-110°C, keep warm and stir for 1-3h, control the temperature at 50-60°C, add sodium hydroxide and calcium oxide, keep warm for 3-6h under stirring, filter and rotary evaporate to obtain component 2;
[0012] S3: In a carbon dioxide atmosphere, add component 2 and benzyltriethylammonium chloride into a reaction kettle and disperse them evenly. Control the temperature at 120-130°C, keep the reaction warm for 9-12 hours, and filter to obtain an adhesive.
[0013] Preferably, the refractory aggregate is a mixture of graphite and talc in a mass ratio of 1:0.5-2.
[0014] Preferably, the suspending agent is one or more of carboxymethyl cellulose and sodium bentonite mixed in any ratio.
[0015] Preferably, the addition ratio of the vinyl silicone component, 3-mercaptopropionic acid, azobisisobutyronitrile and anhydrous ethanol in S1 is 10 g: 2-4 g: 0.55-1.1 g: 10-20 mL.
[0016] Preferably, the addition ratio of component 1, epichlorohydrin, benzyltriethylammonium chloride, sodium hydroxide and calcium oxide in S2 is 10g: 2-4g: 0.1-0.2g: 0.05-0.1g: 0.2-1g.
[0017] Preferably, the mass ratio of the components di and benzyltriethylammonium chloride in S3 is 10:0.2-0.4.
[0018] Preferably, the preparation method of the vinyl silicone component comprises the following steps: adding tetraethyl orthosilicate, ethanol solution and hydrochloric acid solution into a reaction kettle and dispersing them evenly, controlling the temperature at 40-50°C, and keeping the temperature for reaction for 1-3 hours, adding 3-(methacryloyloxy)propyltrimethoxysilane, hydroxyethyl acrylate and anhydrous ethanol, blending them and adding them into the reaction kettle and dispersing them evenly, keeping the temperature for reaction for 1-3 hours, and vacuum filtering to obtain the vinyl silicone component.
[0019] Preferably, the ethanol solution is a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:1-2; the hydrochloric acid solution is a 2.5-5g / mL hydrochloric acid aqueous solution; the addition ratio of tetraethyl orthosilicate, ethanol solution, hydrochloric acid solution, 3-(methacryloyloxy)propyltrimethoxysilane, hydroxyethyl acrylate, and anhydrous ethanol is 10g:3.7-5mL:0.05-0.1mL:2-2.5g:1-1.5g:40-50mL.
[0020] Preferably, the connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation material.
[0021] Beneficial effects of the present invention:
[0022] (1) The present application uses tetraethyl orthosilicate and 3-(methacryloyloxy)propyltrimethoxysilane as precursors and hydroxyethyl acrylate as a surface modifier to undergo a co-hydrolysis condensation reaction to obtain a vinyl silicone component; and utilizes the mercapto group of 3-mercaptopropionic acid to undergo a click reaction with the double bond of the vinyl silicone component to obtain component one; then utilizes epichlorohydrin to epoxidize component one to obtain component two; and finally utilizes component two to carbonate in a carbon dioxide environment to obtain an adhesive.
[0023] The present application utilizes tetraethyl orthosilicate and 3-(methacryloyloxy)propyltrimethoxysilane to blend and prepare an organosilicon sol. During the preparation of the organosilicon sol, intermolecular cross-linking and self-cross-linking interpenetrating polymer networks are carried out to achieve toughening modification and improve the thermal shock resistance of the material. In addition, the vinyl organosilicon component is epoxidized and carbonate groups are added, and polar groups such as hydroxyl groups and carbonates are introduced into the adhesive to improve the flexibility of the material and its adhesion to the surfaces of graphite rings and adapter plates. The adhesive prepared in the present application is bonded to refractory aggregates and suspending agents to obtain a refractory thermal insulation material, which is then coated and bonded to the surfaces of graphite rings and adapter plates. The toughness of the refractory thermal insulation material itself and its high resistance to the material effectively avoid the problem of refractory thermal insulation material falling off during aluminum alloy casting and increase the service life of the material. In addition, its own corrosion resistance effectively avoids the phenomenon of aluminum hanging and ensures the normal progress of aluminum alloy casting.
[0024] (2) The present application uses graphite and talcum powder as raw materials to mix as refractory aggregate of refractory thermal insulation materials; uses any one of carboxymethyl cellulose and sodium bentonite as a suspending agent; and mixes the refractory aggregate, suspending agent and adhesive to obtain refractory thermal insulation materials. Sodium bentonite and carboxymethyl cellulose are added to the refractory thermal insulation materials to effectively buffer the volume expansion effect generated during the generation of new phases, improve the high temperature strength, bonding strength and corrosion resistance of the materials, and improve the fluidity of the materials and their construction performance. DETAILED DESCRIPTION
[0025] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The preparation method of the adhesive of embodiment 1 comprises the following steps:
[0027] S1: 10 g of tetraethyl orthosilicate, 2.5 mL of anhydrous ethanol, 2.5 mL of deionized water, and 0.05 mL of 2.5 g / mL hydrochloric acid aqueous solution were added to a reactor and dispersed evenly, the temperature was controlled at 40°C, and the mixture was kept warm for reaction for 1 h. 2 g of 3-(methacryloyloxy)propyltrimethoxysilane, 1 g of hydroxyethyl acrylate, and 40 mL of anhydrous ethanol were added, blended, and added to a reactor and dispersed evenly. The mixture was kept warm for reaction for 1 h, and vacuum filtered to obtain a vinyl silicone component.
[0028] S2: 10 g of vinyl silicone component, 2 g of 3-mercaptopropionic acid, 0.55 g of azobisisobutyronitrile, and 10 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly to obtain component 1;
[0029] S3: Add 10g of component 1, 2g of epichlorohydrin and 0.1g of benzyltriethylammonium chloride into a reaction kettle and disperse evenly, heat to 100°C, keep warm and stir for 1h, control the temperature at 50°C, add 0.05g of sodium hydroxide and 0.2g of calcium oxide, keep warm for 3h under stirring, filter and rotary evaporate to obtain component 2;
[0030] S4: In a carbon dioxide atmosphere, add 10 g of component 2 and 0.2 g of benzyltriethylammonium chloride into a reaction kettle and disperse them evenly. Control the temperature at 120°C, keep the reaction warm for 9 hours, and filter to obtain an adhesive.
[0031] The preparation method of the adhesive of embodiment 2 comprises the following steps:
[0032] S1: 10 g of tetraethyl orthosilicate, 2.5 mL of anhydrous ethanol, 2.5 mL of deionized water, and 0.07 mL of 2.5 g / mL hydrochloric acid aqueous solution were added to a reactor and dispersed evenly, the temperature was controlled at 45°C, and the mixture was kept warm for 2 h. 2.2 g of 3-(methacryloyloxy)propyltrimethoxysilane, 1.2 g of hydroxyethyl acrylate, and 45 mL of anhydrous ethanol were added to the reactor and dispersed evenly, the mixture was kept warm for 2 h, and the vinyl silicone component was obtained by vacuum filtration.
[0033] S2: 10 g of vinyl silicone component, 3 g of 3-mercaptopropionic acid, 0.8 g of azobisisobutyronitrile, and 15 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly to obtain component 1;
[0034] S3: Add 10g of component 1, 3g of epichlorohydrin and 0.15g of benzyltriethylammonium chloride into a reaction kettle and disperse them evenly. Heat to 100°C, keep warm and stir for 3h, control the temperature at 55°C, add 0.07g of sodium hydroxide and 0.6g of calcium oxide, keep warm for 3h under stirring, filter and rotary evaporate to obtain component 2;
[0035] S4: In a carbon dioxide atmosphere, add 10 g of component 2 and 0.3 g of benzyltriethylammonium chloride into a reaction kettle and disperse them evenly. Control the temperature at 125°C, keep the reaction warm for 9 hours, and filter to obtain an adhesive.
[0036] The preparation method of the adhesive of Example 3 comprises the following steps:
[0037] S1: 10 g of tetraethyl orthosilicate, 2.5 mL of anhydrous ethanol, 2.5 mL of deionized water, and 0.1 mL of 2.5 g / mL hydrochloric acid aqueous solution were added to a reactor and dispersed evenly, the temperature was controlled at 50°C, and the mixture was kept warm for reaction for 3 h. 2.5 g of 3-(methacryloyloxy)propyltrimethoxysilane, 1.5 g of hydroxyethyl acrylate, and 50 mL of anhydrous ethanol were added, blended, and added to a reactor and dispersed evenly. The mixture was kept warm for reaction for 3 h, and vacuum filtered to obtain a vinyl silicone component.
[0038] S2: 10 g of vinyl silicone component, 4 g of 3-mercaptopropionic acid, 1.1 g of azobisisobutyronitrile, and 20 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly to obtain component 1;
[0039] S3: Add 10g of component 1, 4g of epichlorohydrin and 0.2g of benzyltriethylammonium chloride into a reaction kettle and disperse evenly, heat to 110°C, keep warm and stir for 3h, control the temperature at 60°C, add 0.1g of sodium hydroxide and 1g of calcium oxide, keep warm for 6h under stirring, filter and rotary evaporate to obtain component 2;
[0040] S4: In a carbon dioxide atmosphere, add 10 g of component 2 and 0.4 g of benzyltriethylammonium chloride into a reaction kettle and disperse them evenly. Control the temperature at 130° C., keep the reaction warm for 12 h, and filter to obtain an adhesive.
[0041] Embodiment 4 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0042] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0043] A2: 50 g of talcum powder, 25 g of graphite, 20 g of the binder prepared in Example 1, and 5 g of the suspending agent carboxymethyl cellulose were mixed to obtain a refractory heat-insulating material.
[0044] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0045] Embodiment 5 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0046] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0047] A2: 50 g of talcum powder, 25 g of graphite, 20 g of the binder prepared in Example 2, and 5 g of the suspending agent carboxymethyl cellulose were mixed to obtain a refractory heat-insulating material.
[0048] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0049] Embodiment 6 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0050] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0051] A2: 50 g of talcum powder, 25 g of graphite, 20 g of the binder prepared in Example 3, and 5 g of the suspending agent carboxymethyl cellulose were mixed to obtain a refractory heat-insulating material.
[0052] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0053] Embodiment 7 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0054] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0055] A2: 50 g of talcum powder, 25 g of graphite, 15 g of the binder prepared in Example 3, and 5 g of the suspending agent carboxymethyl cellulose were mixed to obtain a refractory heat-insulating material.
[0056] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0057] Embodiment 8 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0058] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0059] A2: 50 g of talcum powder, 25 g of graphite, 25 g of the binder prepared in Example 3, and 5 g of the suspending agent carboxymethyl cellulose were mixed to obtain a refractory heat-insulating material.
[0060] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0061] Comparative Example 1 The preparation method of the adhesive comprises the following steps:
[0062] S1: 10 g of tetraethyl orthosilicate, 2.5 mL of anhydrous ethanol, 2.5 mL of deionized water, and 0.07 mL of 2.5 g / mL hydrochloric acid aqueous solution were added to a reactor and dispersed evenly, the temperature was controlled at 45°C, and the mixture was kept warm for 2 h. 2.2 g of 3-(methacryloyloxy)propyltrimethoxysilane, 1.2 g of hydroxyethyl acrylate, and 45 mL of anhydrous ethanol were added to the reactor and dispersed evenly, the mixture was kept warm for 2 h, and the vinyl silicone component was obtained by vacuum filtration.
[0063] S2: 10 g of vinyl silicone component, 3 g of 3-mercaptopropionic acid, 0.8 g of azobisisobutyronitrile, and 15 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly to obtain component 1;
[0064] S3: Add 10g of component 1, 3g of epichlorohydrin and 0.15g of benzyltriethylammonium chloride into a reaction kettle and disperse evenly. Heat to 100°C, keep warm and stir for 3h, control the temperature at 55°C, add 0.07g of sodium hydroxide and 0.6g of calcium oxide, keep warm for 3h under stirring, filter and rotary evaporate to obtain an adhesive.
[0065] Comparative Example 2 The preparation method of the adhesive comprises the following steps:
[0066] S1: 10 g of tetraethyl orthosilicate, 2.5 mL of anhydrous ethanol, 2.5 mL of deionized water, and 0.07 mL of 2.5 g / mL hydrochloric acid aqueous solution were added to a reactor and dispersed evenly, the temperature was controlled at 45°C, and the mixture was kept warm for 2 h. 2.2 g of 3-(methacryloyloxy)propyltrimethoxysilane, 1.2 g of hydroxyethyl acrylate, and 45 mL of anhydrous ethanol were added to the reactor and dispersed evenly, the mixture was kept warm for 2 h, and the vinyl silicone component was obtained by vacuum filtration.
[0067] S2: 10 g of vinyl silicone component, 3 g of 3-mercaptopropionic acid, 0.8 g of azobisisobutyronitrile, and 15 mL of anhydrous ethanol were added into a reaction kettle and dispersed evenly to obtain an adhesive.
[0068] The preparation method of the adhesive of Comparative Example 3 comprises the following steps:
[0069] S1: 10 g of tetraethyl orthosilicate, 2.5 mL of anhydrous ethanol, 2.5 mL of deionized water, and 0.07 mL of 2.5 g / mL hydrochloric acid aqueous solution were added to a reactor and dispersed evenly. The temperature was controlled at 45°C and the mixture was kept warm for 2 h. 1.2 g of hydroxyethyl acrylate and 45 mL of anhydrous ethanol were added to the reactor and mixed and then dispersed evenly. The mixture was kept warm for 2 h and vacuum filtered to obtain a vinyl silicone component.
[0070] S2: 10 g of vinyl silicone component, 3 g of 3-mercaptopropionic acid, 0.8 g of azobisisobutyronitrile, and 15 mL of anhydrous ethanol were added to a reaction kettle and dispersed evenly to obtain component 1;
[0071] S3: Add 10g of component 1, 3g of epichlorohydrin and 0.15g of benzyltriethylammonium chloride into a reaction kettle and disperse them evenly. Heat to 100°C, keep warm and stir for 3h, control the temperature at 55°C, add 0.07g of sodium hydroxide and 0.6g of calcium oxide, keep warm for 3h under stirring, filter and rotary evaporate to obtain component 2;
[0072] S4: In a carbon dioxide atmosphere, add 10 g of component 2 and 0.3 g of benzyltriethylammonium chloride into a reaction kettle and disperse them evenly. Control the temperature at 125°C, keep the reaction warm for 9 hours, and filter to obtain an adhesive.
[0073] Comparative Example 4 The preparation method of the adhesive comprises the following steps:
[0074] S1: 10 g of tetraethyl orthosilicate, 2.5 mL of anhydrous ethanol, 2.5 mL of deionized water, and 0.07 mL of 2.5 g / mL hydrochloric acid aqueous solution were added into a reactor and dispersed evenly. The temperature was controlled at 45°C and the reaction was kept warm for 2 h. 2.2 g of 3-(methacryloyloxy)propyltrimethoxysilane, 1.2 g of hydroxyethyl acrylate, and 45 mL of anhydrous ethanol were added and blended, then added into a reactor and dispersed evenly. The reaction was kept warm for 2 h, and vacuum filtered to obtain an adhesive.
[0075] Comparative Example 5 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0076] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0077] A2: 50 g of talcum powder, 25 g of graphite, 20 g of the binder prepared in Comparative Example 1, and 5 g of the suspending agent carboxymethyl cellulose were mixed to obtain a refractory heat-insulating material.
[0078] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0079] Comparative Example 6 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0080] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0081] A2: 50 g of talcum powder, 25 g of graphite, 20 g of the binder prepared in Comparative Example 2, and 5 g of the suspending agent carboxymethyl cellulose were mixed to obtain a refractory heat-insulating material.
[0082] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0083] Comparative Example 7 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0084] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0085] A2: 50 g of talcum powder, 25 g of graphite, 20 g of the binder prepared in Comparative Example 3, and 5 g of the suspending agent carboxymethyl cellulose were mixed to obtain a refractory heat-insulating material.
[0086] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0087] Comparative Example 8 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0088] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0089] A2: 50 g of talcum powder, 25 g of graphite, 20 g of the binder prepared in Comparative Example 4, and 5 g of the suspending agent carboxymethyl cellulose were mixed to obtain a refractory heat-insulating material.
[0090] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0091] Comparative Example 9 A mold processing process for hot top casting of aluminum alloy comprises the following steps:
[0092] A1: The connection between the graphite ring and the adapter plate of the hot top casting crystallizer is polished and cleaned before the surface is coated with refractory insulation materials;
[0093] A2: 50 g of talcum powder, 25 g of graphite, and 20 g of the binder prepared in Example 4 were mixed to obtain a refractory heat-insulating material.
[0094] A3: Coat the refractory insulation material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer.
[0095] Performance Testing
[0096] (1) High-temperature sealing property: The refractory heat-insulating materials prepared in Examples 4-8 and Comparative Examples 5-9 were squeezed between two steel cylinders as samples and then placed in a 600°C one-way furnace. After the upper end of the steel cylinder was pressurized to 98N, it was evacuated to 0.05MPa. The time taken for the pressure in the steel cylinder to recover from 0.05MPa to 0.1MPa was measured and recorded as the recovery time S. The test results are shown in Table 1.
[0097] (2) Bonding strength: The refractory insulation materials prepared in Examples 4-8 and Comparative Examples 5-9 were placed on a graphite ring at 800° C. for 30 min as samples, and the bonding strength between the samples and the graphite ring was tested after cooling; the test results are shown in Table 1;
[0098] (3) Slag resistance: The refractory heat-insulating materials prepared in Examples 4-8 and Comparative Examples 5-9 were vibrated into crucible samples (external dimensions 70mmx70mmx70mm, slag hole size 30mmx30mm) by the static crucible method, demolded after hardening, cured at room temperature for 24 hours, and then dried in a drying oven at 110°C for 24 hours. 30g of slag was added to the crucible samples prepared from the refractory heat-insulating materials prepared in Examples 4-8 and Comparative Examples 5-9, and kept at 1500°C for 3 hours. After natural cooling, the crucible was cut symmetrically along the center line of the crucible, and the erosion index was used to evaluate the slag erosion resistance of the castable:
[0099] Erosion index = (SS 0 ) / S 0 x100%
[0100] Where: S is the cross-sectional area of the crucible hole after corrosion, cm 2 , S 0 is the cross-sectional area of the original crucible hole, cm 2; The test results are shown in Table 1;
[0101] (4) Thermal shock resistance: According to YB / T 2206.2-1998, the fire-resistant thermal insulation material samples prepared in Examples 4-8 and Comparative Examples 5-9 were heated to 1000°C in one heating cycle, then immersed in water at room temperature for 3 min, and then placed in front of a fan for 7 min. The above operation was repeated until fracture, and the number of cycles was tested. The test results are shown in Table 1.
[0102] Table 1: Statistical table of performance test data of Examples 4-8 and Comparative Examples 5-9
[0103]
[0104]
[0105] It can be seen from Table 1 that the refractory thermal insulation material prepared in the present application is applied to the connection between the graphite ring and the adapter plate. In the subsequent aluminum alloy casting process, the prepared refractory thermal insulation material has high bonding strength and good thermal shock resistance and corrosion resistance, which not only effectively avoids the problem of refractory thermal insulation material falling off in a high temperature environment; but also effectively blocks the high-temperature aluminum alloy liquid in the crystallizer, avoiding aluminum hanging at the junction of the graphite ring and the adapter plate.
[0106] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A mold processing process for hot top casting of aluminum alloy, characterized in that: The method comprises the following steps: coating a refractory heat-insulating material on the surface of the connection between the graphite ring and the adapter plate of the hot top casting crystallizer; The refractory heat-insulating material comprises the following raw materials in parts by weight: 50-80 parts by weight of refractory aggregate, 15-25 parts by weight of binder, and 2-5 parts by weight of suspending agent; The preparation method of the adhesive comprises the following steps: S1: adding vinyl silicone component, 3-mercaptopropionic acid, azobisisobutyronitrile and anhydrous ethanol into a reaction kettle and dispersing them evenly to obtain component 1; S2: Add component 1, epichlorohydrin and benzyltriethylammonium chloride into a reaction kettle and disperse evenly, heat to 100-110°C, keep warm and stir for 1-3h, control the temperature at 50-60°C, add sodium hydroxide and calcium oxide, keep warm for 3-6h under stirring, filter and rotary evaporate to obtain component 2; S3: In a carbon dioxide atmosphere, add component 2 and benzyltriethylammonium chloride into a reaction kettle and disperse them evenly, control the temperature at 120-130°C, keep the reaction warm for 9-12 hours, and filter to obtain an adhesive; The preparation method of the vinyl silicone component comprises the following steps: adding ethyl orthosilicate, ethanol solution and hydrochloric acid solution into a reaction kettle and dispersing them uniformly, controlling the temperature at 40-50° C., and keeping the temperature for reaction for 1-3 hours, adding 3-(methacryloyloxy)propyltrimethoxysilane, hydroxyethyl acrylate and anhydrous ethanol, blending them, adding them into the reaction kettle and dispersing them uniformly, keeping the temperature for reaction for 1-3 hours, and vacuum filtering to obtain the vinyl silicone component.
2. A mold processing process for hot top casting of aluminum alloy according to claim 1, characterized in that: The refractory aggregate is obtained by mixing graphite and talcum powder in a mass ratio of 1:0.5-2.
3. A mold processing process for hot top casting of aluminum alloy according to claim 1, characterized in that: The suspending agent is one of carboxymethyl cellulose and sodium bentonite or a mixture of the two in any ratio.
4. A mold processing process for hot top casting of aluminum alloy according to claim 1, characterized in that: The addition ratio of the vinyl silicone component, 3-mercaptopropionic acid, azobisisobutyronitrile, and anhydrous ethanol in S1 is 10 g: 2-4 g: 0.55-1.1 g: 10-20 mL.
5. The mold processing process for hot top casting of aluminum alloy according to claim 1, characterized in that: The addition ratio of component 1, epichlorohydrin, benzyltriethylammonium chloride, sodium hydroxide and calcium oxide in S2 is 10g: 2-4g: 0.1-0.2g: 0.05-0.1g: 0.2-1g.
6. The mold processing process for hot top casting of aluminum alloy according to claim 1, characterized in that: The mass ratio of component II and benzyltriethylammonium chloride in S3 is 10:0.2-0.
4.
7. A mold processing process for hot top casting of aluminum alloy according to claim 1, characterized in that: The ethanol solution is obtained by mixing anhydrous ethanol and deionized water in a volume ratio of 1:1-2; the hydrochloric acid solution is a 2.5-5g / mL hydrochloric acid aqueous solution; the addition ratio of tetraethyl orthosilicate, ethanol solution, hydrochloric acid solution, 3-(methacryloyloxy)propyltrimethoxysilane, hydroxyethyl acrylate, and anhydrous ethanol is 10g:3.7-5mL:0.05-0.1mL:2-2.5g:1-1.5g:40-50mL.
8. The mold processing process for hot top casting of aluminum alloy according to claim 1, characterized in that: The graphite ring and adapter plate joints of the hot top casting crystallizer are polished and cleaned before the surface is coated with refractory insulation material.
Citation Information
Patent Citations
Method for preparing nano silicon / polyacrylate composite emulsion
CN102030873A
Organic-inorganic hybrid gradient wetting coating and preparation method thereof
CN102433054A